Validity of Ankle Brachial Index using Palpation Method in Screening for Peripheral Arterial Disease in Type 2 Diabetes Mellitus Patients at a Tertiary Hospital in the Philippines - Mercado, Jonathan (J ASEAN Fed Endocr Soc, 2018)
INTRODUCTION: Peripheral Artery Disease (PAD) is a significant marker of cardiovascular disease and is prevalent but underdiagnosed. Ankle-Brachial Index (ABI) is the recommended screening test for PAD. However, not all clinics have a Doppler ultrasound. ABI by palpation offers a more feasible alternative. OBJECTIVE: This study aims to determine the validity of ABI measurement by palpation method in the screening of PAD. METHODOLOGY: This prospective validation study utilized a cross-sectional analytic design. Three physicians performed the ABI by palpation method and their result was compared to the Doppler ABI. The accuracy indices for validation was computed per physician conducting the ABI by palpation and also as an average of all 3 palpation method readings. During the course of sampling, there were no patients with severe PAD found during the prospective period. RESULTS: The accuracy of Ankle Brachial Index using Palpation method yielded the following ranges, sensitivity between 63.16 % - 73.68%, specificity of 94.06% - 98.02%, PPV within 85.37% - 95.45%, and NPV within 80.73% - 86.84% in predicting PAD. The accuracy indices were clinically acceptable. Meanwhile, the raters’ usage of Ankle Brachial Index using Palpation method demonstrated a substantial agreement with ABI by Doppler Method performed by the angiologist (Cohen Kappa >0.60). CONCLUSION: The ABI by palpation is a good screening tool for PAD, but the person performing it must be adequately trained to do the procedure. The procedure is affordable and convenient, and should be done routinely during clinic visits in the physical examination of patients with known risk factors for PAD.